Development of E-Module Based Ethno-STEM to Improve HOTS and Students' Scientific Attitudes in Chemistry Learning - Betzy Ayu Omega Rampean; Erwinda Gracya Laman; Widi Aprilia Ta'bi; Chelsea Senolinggi; Tirza Marsena; Fikra Nugraha (Jurnal Pendidikan Kimia Indonesia, 2025)
21st-century learning aims to produce quality, superior, and competitive human resources. In this digital era, teachers must be able to master technology and some intelligent media usage. Digital-based media integrated with science has been widely applied in education to increase student motivation in chemistry learning compared to conventional learning. Therefore, learning is not only limited to the classroom as a transfer of knowledge, but also requires support that is able to develop students' skills and attitudes in living in the 21st century. One example of skills and attitudes that must be possessed in the 21st century is higher-order thinking skills (HOTS) and scientific attitudes. E-modules based on ethno-stem developed with heyzine flipbooks presenting reaction rate material related to Toraja culture, specifically the typical Pa'piong food, aims to improve (HOTS) and scientific attitudes of students. This research is a development research with the ADDIE model, namely analysis, design, development, implementation, and evaluation. E-modules based on ethno-stem were validated and revised by 4 experts, namely media experts, material experts, language, and cultural experts, as well as 2 teachers who gave a score of 0.91 on the assessment scale and categorized as sss very valid. The sample in this study, namely 65 students, gave an average score of 94, which stated that it was very practical.